Pelatihan Penulisan Karya Tulis Ilmiah Untuk Meningkatkan Kompetensi Guru Madrasah Ibtidaiyah - Ika Rachmawati; Anna Widayani (Universitas Mathla'ul Anwar Banten, 2022)
ACADEMIC WRITING TRAINING TO IMPROVE MADRASAH IBTIDAIYAH TEACHER COMPETENCE. Teachers can benefit from writing scientific articles in various ways, including improving their writing abilities, sharpening their thinking, and broadening their views. Scientific papers that have been presented or published can also help with the credit scores appraisal for teacher promotions. Because the creation of scientific papers plays such a significant role in enhancing teacher professionalism and advancing their functional positions, it is crucial to provide teachers with training and aid in writing scientific papers. This activity aims to provide teachers with knowledge of the rules for writing scientific papers, raise awareness by compiling scientific papers, improve their competence as professional teachers, the quality of their students, and the ability to write scientific papers. This program was attended by 15 teachers from Madrasah Ibtidaiyah Darussalam in Blitar City. It was implemented in two stages, namely the counseling stage and the training stage. All of the goals established for this activity can be achieved properly, based on the results of direct observation throughout the activities and questionnaires filled out by participants.